If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -3x = -15 Solving 4 + -3x = -15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3x = -15 + -4 Combine like terms: 4 + -4 = 0 0 + -3x = -15 + -4 -3x = -15 + -4 Combine like terms: -15 + -4 = -19 -3x = -19 Divide each side by '-3'. x = 6.333333333 Simplifying x = 6.333333333
| 3(x-5)=57-5x | | 1000+600+6x=750+400+9x | | 2x-8=96-11x | | 15-y=13 | | 6-6k-2k= | | 2*(x+3)=8 | | 0=x^2+4x-3 | | 2(3x+4)=3x+2[3(x-1)+2] | | 1*2=2 | | 5*(x+19)= | | 2(3x+4)=3x+2[3x-10+2] | | 22+r=37 | | 2(z+1)=3z+3 | | 6y-2.1=y-2.1 | | 9x+8=48+5x | | 1200+45b=1800+60b | | 7b+5=4b+6 | | a+b=1000 | | 7+5=4+6 | | 4x=2-5x | | 3y+18=7y-6 | | 3x-4(5x-7)+5=12x-7(5+8x)+10 | | X+2x+8=8+2x+x | | 2x+3k=1 | | 3x+1=3x-2 | | 5a+13b=80000 | | 3d+4=7d+8 | | (2+y)/3=-1 | | -20=7y-3y+4 | | 14-14-b=19-14 | | (z+10)/9=2 | | 6y+8y-7=-7 |